2015
DOI: 10.1039/c5dt00288e
|View full text |Cite
|
Sign up to set email alerts
|

[1,1-(η2-dppe)-3-(NC5H5)-closo-1,2-RhSB9H8]: conformational lability and reactivity with H2 upon protonation

Abstract: Metallaheteroboranes are versatile compounds that can be conveniently modified and eventually tailored by ligand modification at either the metal centre or the boron vertices. Recently, we have discovered that protonation of some rhodathiaboranes affords cationic clusters with interesting reaction chemistry. In order to tune the reactivity of some of these polyhedral boron-based compounds, we have prepared air-stable orange [1,1-(η(2)-dppe)-3-(NC5H5)-closo-1,2-RhSB9H8] (2) by the treatment of the known hydrido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 27 publications
(91 reference statements)
1
19
0
Order By: Relevance
“…The developments towards large numbers of metallaheteroboranes have gained a good deal of interest, owing to their utility in the preparation of high‐nuclearity clusters . Among them, group 9 metallaheteroboranes have received significant attention, due to their applications in catalysis , . For example, nido ‐rhodathiaborane [8,8,8‐(PPh 3 ) 2 H‐9‐(NC 5 H 5 )‐ nido ‐8,7‐RhSB 9 H 9 ] acts as a catalyst for the isomerization and hydrogenation of alkenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developments towards large numbers of metallaheteroboranes have gained a good deal of interest, owing to their utility in the preparation of high‐nuclearity clusters . Among them, group 9 metallaheteroboranes have received significant attention, due to their applications in catalysis , . For example, nido ‐rhodathiaborane [8,8,8‐(PPh 3 ) 2 H‐9‐(NC 5 H 5 )‐ nido ‐8,7‐RhSB 9 H 9 ] acts as a catalyst for the isomerization and hydrogenation of alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nido ‐rhodathiaborane [8,8,8‐(PPh 3 ) 2 H‐9‐(NC 5 H 5 )‐ nido ‐8,7‐RhSB 9 H 9 ] acts as a catalyst for the isomerization and hydrogenation of alkenes. [8c] Although metallaheteroboranes comprised of thia, , , and aza[4b] ligands have been explored, compounds that contain heavier heteroatoms, such as selenolato and tellurolato ligands, are relatively limited. As a result, we[5a], [5b], [5c], and others have synthesized interesting metallaheteroborane clusters containing selenium and tellurium that illustrate reactivity and structural patterns different from those containing sulfide …”
Section: Introductionmentioning
confidence: 99%
“…71, 65 and 71°, respectively (Figure a). This twist of the M{(L) 2 } moiety with respect the {SB 9 H 9 } fragment is a common structural feature in 11‐vertex metallaheteroboranes that incorporate {M(L) 2 } (M = Rh,[8g] Ir, Pt, Pd) groups. A larger ϕ angle of 81° is found in the 9‐vertex nickellathiaborane [7,7‐(dppe)‐ arachno ‐6,8‐NiS 2 B 6 H 8 ], in which the {Ni(dppe)} moiety is bound to the {S 2 B 6 H 9 } unit in a tetrahapto fashion (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…This exploratory synthetic work is completed by studies of the reactivities of the new nickellathiaboranes with small molecules such as NH 3 and CO and the comparison of their reactivities with those exhibited by the rhodathiaboranes that we reported in recent years ,. [7e], In this regard, this work also includes new reactivity studies between ammonia and the previously reported iridathiaborane [(PMe 3 ) 2 ‐ isonido ‐IrSB 9 H 10 ][8m] and its PMe 2 Ph‐ligated counterpart, [(PMe 2 Ph) 2 ‐ isonido ‐IrSB 9 H 10 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation